2017
DOI: 10.1016/j.jpeds.2016.11.075
|View full text |Cite
|
Sign up to set email alerts
|

Crystalloid Fluid Choice and Clinical Outcomes in Pediatric Sepsis: A Matched Retrospective Cohort Study

Abstract: Objective To test the hypothesis that resuscitation with balanced fluids (lactated Ringer [LR]) is associated with improved outcomes compared with normal saline (NS) in pediatric sepsis. Study design We performed matched analyses using data from 12 529 patients <18 years of age with severe sepsis/septic shock at 382 US hospitals between 2000 and 2013 to compare outcomes with vs without LR as part of initial resuscitation. Patients receiving LR were matched 1:1 to patients receiving only NS (NS group), includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 39 publications
0
33
0
3
Order By: Relevance
“…Rationale: Increasing evidence from observational studies and RCTs in adults suggests that resuscitation with crystalloid fluids containing high chloride concentrations (e.g., 0.9% saline) is associated with hyperchloremic acidosis, systemic inflammation, acute kidney injury (AKI), coagulopathy, and mortality when compared with resuscitation with more balanced/buffered crystalloids (e.g., lactated Ringer's, PlasmaLyte) [192]. Although no pediatric RCTs compare balanced/ buffered crystalloids to 0.9% saline, there are two large observational studies in children with sepsis [193,194]. They included a total of 30,532 children with sepsis, 2100 of whom received only balanced/buffered crystalloids for the first 72 h of hospital admission, and 28,432 who received 0.9% saline (Supplemental Table 5, Supplemental Digital Content 1, http://links .lww.com/ PCC/B139).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rationale: Increasing evidence from observational studies and RCTs in adults suggests that resuscitation with crystalloid fluids containing high chloride concentrations (e.g., 0.9% saline) is associated with hyperchloremic acidosis, systemic inflammation, acute kidney injury (AKI), coagulopathy, and mortality when compared with resuscitation with more balanced/buffered crystalloids (e.g., lactated Ringer's, PlasmaLyte) [192]. Although no pediatric RCTs compare balanced/ buffered crystalloids to 0.9% saline, there are two large observational studies in children with sepsis [193,194]. They included a total of 30,532 children with sepsis, 2100 of whom received only balanced/buffered crystalloids for the first 72 h of hospital admission, and 28,432 who received 0.9% saline (Supplemental Table 5, Supplemental Digital Content 1, http://links .lww.com/ PCC/B139).…”
mentioning
confidence: 99%
“…They included a total of 30,532 children with sepsis, 2100 of whom received only balanced/buffered crystalloids for the first 72 h of hospital admission, and 28,432 who received 0.9% saline (Supplemental Table 5, Supplemental Digital Content 1, http://links .lww.com/ PCC/B139). These studies showed that use of balanced/ buffered crystalloids was associated with lower mortality (OR, 0.79; 95% CI, 0.65-0.95) but not AKI (OR, 0.98; 95% CI, 0.94-1.02) [193,194]. Indirect evidence from adult patients, including two large RCTs, also demonstrates benefit with balanced/buffered crystalloids over 0.9% saline, with adult patients who received larger volumes of fluid and those with sepsis exhibiting the greatest benefit [192,195].…”
mentioning
confidence: 99%
“…In a recent large matched cohort study on pediatric sepsis, LR resuscitation was not associated with reduced mortality, AKI, or dialysis even when matched by fluid volume and proportionate LR utilization ( 101 ). Mortality increased with larger fluid volumes and decreased with a greater proportion of fluid given as LR, but there were no differences between LR and NS groups after matching within volume quartiles, by proportionate LR utilization, or in the separate matched analysis of LR-only patients.…”
Section: Fluids: Type In Critically Ill Children?mentioning
confidence: 99%
“…The largest benefit was observed in adults with sepsis. However, no trial has compared the effectiveness of different crystalloid fluid types for resuscitation in children with sepsis, and the two largest observational pediatric studies reported conflicting results . Consequently, there is insufficient evidence to strongly recommend a specific crystalloid fluid type for resuscitation of children with septic shock …”
mentioning
confidence: 99%